Tourism-Based Socio-Economic Transformation of Urban Communities in Kota Yogyakarta - Dwi Antoro, Susanto; Agus Tri Basuki; Ahmad Ma’ruf (Jurnal Ekonomi Manajemen Sistem Informasi, 2026)
This study aims to examine the socio-economic transformation of urban communities in Kota Yogyakarta driven by tourism development, focusing on the effects of tourism activity intensity, economic involvement, and infrastructure support. A quantitative approach was applied using a survey of 124 respondents consisting of MSME actors, tourism workers, and local residents. Data were collected through validated Likert-scale questionnaires and analyzed using multiple linear regression, preceded by classical assumption tests. Hypotheses were tested using t-tests, F-tests, and the coefficient of determination (R²). The results show that tourism activity intensity (β = 0.390; t = 7.641; Sig. 0.000), economic involvement (β = 0.361; t = 7.748; Sig. 0.000), and infrastructure support (β = 0.295; t = 5.869; Sig. 0.000) have positive and significant effects on socio-economic transformation. Simultaneously, the variables significantly influence the dependent variable (F = 295.170; Sig. 0.000). The model demonstrates strong explanatory power (R² = 0.881), indicating that 88.1% of socio-economic transformation is explained by the three variables. The study is limited to one urban area and selected variables. The findings highlight the importance of inclusive and sustainable tourism policies. This research provides empirical quantitative evidence of tourism-driven urban socio-economic transformation in Indonesia.